Phenotypic and Molecular Detection of Carbapenemase-Producing Acinetobacter baumannii Strains from Clinical Specimens in Dezful Teaching Hospital - Behnaz, Deihim; Khorramizadeh, Maryam (Majalah Kedokteran Bandung, 2024)
Nowadays, antibiotic resistance in bacteria has become a global problem. Therefore, the identification of resistant strains of bacteria has attracted special attention in a pursue to choose more effective treatment solutions. One of the most common mechanisms of resistance is the production of carbapenemase enzyme in Acinetobacter baumannii. This present study aimed to detect carbapenemase-producing strains by phenotypic and molecular methods in clinical specimens collected in Ganjavian Hospital of Dezful between June 2021 and May 2022. Antimicrobial susceptibility testing was performed using the Kirby-Bauer disk diffusion and Etest assay, while the extended-spectrum beta-lactamase production (ESBLs) and Metalobetalactamases (MBLs) were detected by combined disk method using ceftazidime and ceftazidime/clavulanic acid disks and imipenem and imipenem /EDTA disks, respectively. Molecular detection of blaIMP, blaSPM, blaOXA-23, and blaOXA-24, blaOXA-58, blaGES genes was performed. Of a total of 54 strains, the highest resistance rate was for cephalosporins (98.1%), and ciprofloxacin (94.2%), in contrast to minocycline (13%). ESBL and MBL producers were 26% and 80%, respectively. All isolates had intermediate resistance against colistin. The most prevalent gene in the carbapenem-resistant A. baumannii (CRAB) was blaOXA-23, followed by blaOXA-24, blaGES, blaIMP, and blaOXA-58 genes. Present report highlights the existence of CRAB and intermediate resistance to colistin and also the co-existence of several genes from different carbapenemase classes in this region. Therefore, resistant strains should be identified promptly and specific treatment protocols should be devised to control the dissemination of resistance genes in therapeutic settings.